Removal of fluoroquinolone contaminants from environmental waters on sepiolite and its photo-induced regeneration. (May 2016) - Sturini, Michela; Speltini, Andrea; Maraschi, Federica; Profumo, Antonella; Tarantino, Serena; Gualtieri, Alessandro F.; Zema, Michele
Abstract: Sepiolite is studied as sorbent for removal of Fluoroquinolone (FQ) contaminants from water. Marbofloxacin (MAR) and Enrofloxacin (ENR) were chosen as model FQs since they are the two most commonly employed veterinary FQs in livestock farming in northern Italy. Adsorption experiments on two sepiolites (SP-1 and SSE16) were carried out in tap water at pH 7.5 to better mimic real conditions. The sorption experimental data were fitted by Freundlich, Langmuir and S-Logistic1 models. The latter better described MAR and ENR adsorptions. Adsorption capacities of SP-1 and SSE16, respectively, were 132 mg g −1 and 121 mg g −1 for MAR, and 112 mg g −1 and 93 mg g −1 for ENR. X-ray powder diffraction, performed on clay samples enriched with each FQ and on the pristine clays, showed no substantial differences between the two sepiolites and evidenced no significant structural changes after FQs uptake, as also verified by infrared spectroscopy. This indicates that adsorption occurs only on the external surface of the mineral and not in the intracrystalline microporosity, likely due to the interaction between the FQ carboxylic group and the sepiolite surface. For the first time solid-state photodegradation of the adsorbed FQs was investigated for regenerating the sorbent. Results showed that the adsorbed drugs are effectively photodegraded by solar light, thus allowing sepiolite to be reused. The efficiency of this material for remediation of contaminated water was proved on ditch water, collected downstream a swine farm, containing some tens of ng L −1 of MAR and ENR. Highlights: MAR and ENR fluoroquinolones (FQs) adsorption on sepiolite was studied in water. S-logistic1 sigmoidal model best fits experimental data for both FQs. Solid-state photodegradation of FQs adsorbed on sepiolite was tested. Sunlight-induced photodegradation profiles over irradiation time were traced.